From operating room to circuit mechanisms: Clinical basic science partnerships as a strategic model for human neuroscience - Karl Roessler (Epilepsia, 2026)
Abstract Epilepsy surgery offers a unique opportunity to connect clinical care with fundamental research on the human brain. Tissue resected as part of indicated surgical treatment can be studied using electrophysiology, imaging, transcriptomics, proteomics, connectomics, and computational modeling without altering the clinical procedure or exposing patients to additional risk. Close partnerships between high‐volume epilepsy surgery centers and basic neuroscience laboratories can therefore provide direct insight into human neuronal and circuit function that cannot always be obtained from animal models. Recent work identifying distinctive connectivity rules within the human hippocampal CA3 network illustrates the scientific potential of this approach. We propose that epilepsy surgery programs should serve as clinical hubs within structured, ethically governed translational networks that integrate patient care, tissue acquisition, neurophysiology, molecular biology, and computational neuroscience. Although epilepsy surgery currently provides the most mature framework, the same model may be extended to other neurosurgical procedures in which viable human brain tissue becomes available. Such partnerships could accelerate mechanistic discovery and improve the relevance of basic neuroscience to epilepsy and other neurological disorders.